PENGARUH VARIASI FRAKSI VOLUME KOMPOSIT SERAT SABUT KELAPA UNSATURATED-POLYESTER TERHADAP PENGUJIAN TARIK - Aulia Hifani Ramanda; Sembada varian Iqbal; Pambudi Fajar Rakhmad; Dermawan Rifki Waldy; Musaffa Salam Qodirun (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
The development of composite materials in recent years is very rapid. One of them is coco fiber as a material of natural fiber composite amplifier. The benefits of coco fiber coated composites are available, easy raw materials, low density, and easy machining processes. The purpose of this research is to know the mechanical properties of tensile strength with coco fiber reinforcement. In the application of coconut fiber composite engineering products can be used as household, desk panel, ethernet and gypsum. fabrication of coconut fiber-reinforced composites with unsaturated resin-polyester structures as a matrix and coco fiber orientation as reinforced. Variation of volume fraction of composite fiber 0%, 5%, 7,5%, and 10%. The results of this study indicate the fraction of the volume of 7.5% fiber in composites that have tensile test results of 20.2 MPa. While the volume fraction of 10% fiber on composite has the lowest yield of 10.47 Mpa. Keywords: coco fiber composite, hand lay-up, composite volume fraction